2007
DOI: 10.1097/01.meg.0000250585.53608.3c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of liver lesions by real-time contrast-enhanced ultrasonography

Abstract: Real-time contrast-enhanced ultrasonography provides sensitive and specific criteria for the differential diagnosis between benign and malignant liver lesions, and in most cases it may replace more expensive and invasive imaging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 48 publications
3
39
1
2
Order By: Relevance
“…[10][11][12][13][14][15]24 This discrepancy may be due to the smaller nodule size in our patients (median size 32 mm) compared to other series. Larger tumors usually develop a central fibrotic area, justifying the peripheral, rim-like arterial contrast uptake in larger tumors.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…[10][11][12][13][14][15]24 This discrepancy may be due to the smaller nodule size in our patients (median size 32 mm) compared to other series. Larger tumors usually develop a central fibrotic area, justifying the peripheral, rim-like arterial contrast uptake in larger tumors.…”
Section: Discussioncontrasting
confidence: 79%
“…4,23 The European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) has recently published updated clinical practice recommendations for CEUS and they suggested that the typical enhanced pattern for cholangiocarcinoma is a rim-like enhancement (or nonenhancement) during the arterial phase followed by hypo/nonenhancement during the portal and delayed phases. 24 However, these recommendations are based on case-series of limited number of patients, [13][14][15] most of them noncirrhosis, with large tumors. In addition, in a recent prospective study CEUS misdiagnosed a 16-mm ICC as HCC due to the detection of complete arterial contrast enhancement followed by washout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported that contrast enhanced ultrasonography provides sensitive and specific criteria for the differentiation between malignant and benign liver lesions [12][13][14][15] . Preliminary data for cholangiocarcinoma suggest a behavior that is not dissimilar to metastatic lesions [14,16] . However, the limited number of cases in the reported series does not allow conclusive considerations for cholangiocarcinoma.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Studies have demonstrated that CEUS is capable of increasing sensitivity and specificity in detection of malignant hepatic masses compared to B-mode US, citing its advantages in capturing liver perfusion phase patterns to better delineate lesion borders from the surrounding parenchyma (11)(12)(13)(14)(15)(16)(17). This led to approval of one US contrast agent for characterization of FLL in adult as well as pediatric patients by the U.S. Food and Drug Administration in April 2016 (18).…”
Section: Introductionmentioning
confidence: 99%